Ecstasy use in secondary school students in Turkey - Ögel, Kültegin; Çorapçıoğlu, Aytül; Tot, Şenel; Doğan, Orhan; Sır, Aytekin; Bilici, Mustafa; Tamar, Defne; Uğuz, Şükrü; Yenilmez, Çınar; Tamar, Müge (Journal of Dependence, 2003)
Objective: To detect prevalence of ecstasy use and to investigate the characteristics of ecstasy users in secondary school students in Turkey. Method: In this study, data collected from 11.991 tenth grade students from 9 large provinces from different geographic regions. Results: Life-time prevalence of ecstasy use was found to be 2.5%. The mean age of first use of ecstasy was 13.4 ± 1.9 years. The highest prevalence of ecstasy use has been observed in ages of 20 years or older. The city the most frequest use was seen was İzmir. More than half of ecstasy user has reported that they used other substances, as well, and they had a user in close relatives. Prevalence was higher in private schools than other type of schools. Among students who used ecstasy at least once, 49.5% reported that they believed that regular cannabis use had no or nonsignificant harm, 55.6% reported that they believed that use of heroin once had no or nonsignificant harm. Conclusion: It has been concluded that, although prevalence of ecstasy use among young people is lower than European countries, it’s quite high in special populations with high social and economic status and that are similar to western populations.